The effect of visible light ratio and amino acids in some biochemical growth parameters of chrysanthemum indicum plants under various irrigation periods - Bdewi , Mawj M.; Kadhim, Ahmed A. (Journal of Kerbala for Agricultural Sciences, 2024)
An experiment was conducted under plastic shades set up for this purpose in the almussaib city (45 km north of Babil province) During the period from April 1, 2023, to November 15, 2023 to improve biochemical indicators for chrysanthemum plants Minngopher variety with red flowers, the experiment include three factors the first factor different percentages of visible light blocking (50 ,75) % representation of the second factor treating plants with three Irrigation Intervals (daily, every 24 hours, and every 48 hours) as for the third factor spraying plants with many concentrations of free amino acids (0, 1.00, 1.50 and 2.00) mg L-1, a factorial experiment applied using a Randomized Complete Blocks Design with three replicates per treatment. Each replicate contained three pots, with one plant. The results showed the study factors have significant impact of the studied qualities, the interaction (75% shading, daily irrigation, and a concentration of 150 mg L-1) give significant impact in the chlorophyll content of the leaves (44.45 SPAD) while achieved the triple interaction treatment (75% shading, daily irrigation, and treatment with a concentration of 200 mg L-1) significant impact in Nitrogen content of the leaves (3.050%) and phosphorus (0.9027%) and potassium (2.086%) and carbohydrates (29.88%) while for the proline content of the leaves the interactions treatment was impact (50% shading, irrigation every 48 hours and comparative treatment (0.9027 mg g-1) from here we conclude that shading ratios play an important role in reducing the impact of stress intensity humidity and thermal associated with treating plants with free amino acids spraying on vegetative plant.